Peran Social Media Officer pada Akun @Bukaproject dalam Membangun Brand Awareness - Azzahra, Heyssa Itsara; Ramdani, Guruh; Fachrurizzal, Fikry (KOMUNIKA, 2026)
This study examines the role of the Social Media Officer (SMO) in managing the @bukaproject Instagram account to build brand awareness for Buka Project, a creative industry company located in Bogor, using the Honeycomb Model framework approach. This study used a descriptive qualitative method through participant observation, in-depth interviews, and document studies during the internship period. The analysis results show that of the seven Honeycomb functional blocks, Buka Project's social media officer strategy relies predominantly on three main elements: Identity (maintaining visual consistency and tone of voice), Sharing (systematic content distribution based on content mapping), and Relationships (managing production team collaboration and audience interaction). The implementation of this strategy has proven effective in strengthening brand recognition, as evidenced by a 217.2% increase in account reach and the stability of user interaction. The study concludes that the success of the SMO lies not only in the technical aspects of scheduling, but also in the ability to maintain content quality (media richness), work integration between divisions, and data-based performance evaluation.